Policy Recommendations - von Grebmer, Klaus; Bernstein, Jill; Nabarro, David; Prasai, Nilam; Amin, Shazia; Yohannes, Yisehac; Sonntag, Andrea; Patterson, Fraser; Towey, Olive; Thompson, Jennifer (Welthungerhilfe, 2016)
The 17 Sustainable Development Goals (SDGs) in the 2030 Agenda are inextricably linked with one another. To reach Goal 2: End hunger, achieve food security and improved nutrition, and promote sustainable agriculture, there must also be progress on the 16 other SDGs. With that in mind, the following recommendations emphasize the ways we can accelerate toward Zero Hunger in the context of the 2030 Agenda.